2015
DOI: 10.1016/j.fuel.2015.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Esterification of fatty acids with ethanol over layered zinc laurate and zinc stearate – Kinetic modeling

Abstract: h i g h l i g h t sModeling of long chain FFA with ethanol was performed using EleyRideal approach. No diffusional limitations were found with zinc carboxylic salts. High hydrophobic behavior was observed with zinc laurate. Ethanolysis of FFA reached 92% and catalytic gain compared to blanks reached 40%. Structural changes in the catalyst were observed which exchange FFA with the medium. g r a p h i c a l a b s t r a c t a b s t r a c tThis work is focused on the esterification of fatty acids (commercial oleic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…In addition, it is important to mention that the esterification route can also be used to feedstock with moderate free acidity as pre-treatment step in the framework of a conventional transesterification process [11]. Besides the biodiesel production, esterification of short and long chain carboxylic acids is an important route to produce including alkyl esters that are a very important class of chemicals covering a vast variety of applications such as flavors, perfumes, plasticizers, pharmaceuticals, solvents and chemical intermediates [13][14][15][16][17][18]. For esterification of carboxylic acids with alcohols in presence of acid catalysts, both homogeneous and heterogeneous catalysis have been used [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is important to mention that the esterification route can also be used to feedstock with moderate free acidity as pre-treatment step in the framework of a conventional transesterification process [11]. Besides the biodiesel production, esterification of short and long chain carboxylic acids is an important route to produce including alkyl esters that are a very important class of chemicals covering a vast variety of applications such as flavors, perfumes, plasticizers, pharmaceuticals, solvents and chemical intermediates [13][14][15][16][17][18]. For esterification of carboxylic acids with alcohols in presence of acid catalysts, both homogeneous and heterogeneous catalysis have been used [19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several studies involving the use of heterogeneous catalysis have been presented in the literature, which it has been used in the different esterification reactions, such as ion exchange resins [11,19,[22][23][24][25][26], zeolites [27,28], different clay minerals [26,[29][30][31][32][33][34]12] and layered compounds [18,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…A 2.94 w % quantity of CaO-Al 2 O 3 /ZrO 2 mixed oxide was used as a heterogeneous catalyst to transesterify waste cooking oil, achieving 93.48% conversion under a reaction temperature of 120 • C, a 15.64:1 methanol-oil molar ratio, and 4 h reaction time [14]. Although zeolites have numerous advantages over other heterogeneous catalysts, another study found that its catalytic activity in transesterification reactions using a pure mix of fatty acids reached 92% conversion, lower than results above [15].…”
Section: Introductionmentioning
confidence: 93%
“…11,24,25 After cooling the system, the catalyst is restructured and separated after the removal of isopropanol in excess, which was used during the reaction. This catalyst melting/dispersion occurs inside the reactor, even under the influence of pressure generated internally by the vapor from the more volatile component in the media, in this case the alcohol used in the reaction.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…Although the catalyst was recovered after each catalytic cycle, it is important to emphasize that the catalytic activity experiments were carried out at temperatures higher to the phase transitions observed in Figure 5, so the zinc octanoate is "melted" in the reaction media, acting approximately in a hydrophobic homogeneous way, just like what occurs for other layered carboxylates. 11,25,32 Figures 6A and 6B show the 13 C NMR spectra of synthesized zinc octanoate, as well as the compound which was recovered from esterification reactions and submitted to heat treatment at 140 °C.…”
Section: Tests For Reuse Of Zinc Octanoatementioning
confidence: 99%